The Relationship Of Nurses' Compliance In Implementing Standard Operating Procedures (SPO) For Installing Infusations With The Incident Of Phlebitis In The Inpatient Room RSI Mabarrot MWC NU Bungah - Puspita , Uci Nurhayati; Abdul Muhith; Siti Nur Hasina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
The incidence of phlebitis will increase along with poor infusion insertion actions or not in accordance with hospital SPO. This study aims to analyze the relationship between nurse compliance in the implementation of infusion SPO with the incidence of phlebitis in the inpatient room. This study used a cross sectional approach. The sampling technique used in this study used total sampling with a sample size of 22 nurses and 22 inpatients at RSI Mabarrot MWC NU Bungah in February 2024. The instruments used in this study were observation sheets for compliance with SPO for infusion and VIP (Visual Infusion Phlebitis) screening sheets to measure the occurrence of phlebitis. The results showed that out of 22 nurses, 20 nurses were compliant with SPO for infusion with 18 patients (72.7%) not experiencing phlebitis, and 4 patients (18%) patients experiencing phlebitis. The results of data analysis showed a significance value of 0.015 <0.05, which means that there is a relationship between nurse compliance in implementing SPO infusion with the incidence of phlebitis in patients. The compliance of nurses who carry out the SPO for infusion installation will obediently reduce the incidence of phlebitis in patients. It is recommended for nurses to always improve compliance with infusion installation according to the SPO set by the hospital to minimize the occurrence of phlebitis in patients during hospitalization.